Detection of the Interdependence of Economic Development and Environmental Performance at the Industry Level - Nina Ilysheva; Elena Karanina; Elena Baldesku; Ulugbek Zakirov (Montenegrin Journal of Economics)
The aim of the research is to identify the connection between economic development and environmental performance at the industrial level. The subject of the research is a set of processes of correlation analysis of economic and environmental indicators of the oil and gas producing industry. The urgency of the task of mitigating anthropogenic climate change caused by rising concentrations of greenhouse gases in the atmosphere is proven. Statistical data on emissions for the past 15 years are analyzed, change trends are identified. The authors establish the cause of the growth in greenhouse gas emissions, the energy sector being the main contributor. A description of the mechanism of the effect of greenhouse gases on the climate system is provided. The requirements set by international agreements and Russian documents aimed at reducing greenhouse gas emissions are unified. The main gases that cause the greenhouse effect are identified, their classification and brief characteristics are provided in the article. The necessity to promote the monitoring of greenhouse gas emissions and reporting system at the global level is substantiated. The purpose of the advanced metering system is to obtain relevant and reliable data for timely response to and planned reduction of greenhouse gas emissions. In accordance with the recommendations of the international standard for non-financial reporting, GRI, the effectiveness of reducing greenhouse gas emissions should be disclosed in the aspect of “Emissions”. The progress of economic science has made it important to take into account the natural component, and the value of bioresources will increase over time, therefore, the company's economic development can not be isolated. In accordance with the hypothesis, it is assumed that the economy and ecology are interrelated and affect each other.